2015
DOI: 10.35790/ecl.3.1.2015.7823
|View full text |Cite
|
Sign up to set email alerts
|

Tingkat Kecemasan Pada Pasien Penyakit Ginjal Kronik (Pgk) Yang Menjalani Hemodialisis Di Blu Rsup Prof. Dr. R. D. Kandou Manado

Abstract: : Anxiety is often complained of by patients with Chronic Kidney Disease (CKD) undergoing hemodialysis process. This study aimed to determine the level of anxiety among patients with CKD who underwent hemodialysis in Prof. Dr. R. D. Kandou Hospital Manado. This was a descriptive study using survey method. Sanples were patients with CKD who underwent hemodialysis and fulfiled the inclusion and exclusion criteria. The results showed that there were 40 respondents. The majority of respondents that experienced anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 0 publications
1
8
1
13
Order By: Relevance
“…Our study showed that the development of emotion regulation can explain the mechanism of daily influence that is stable throughout adulthood. The researchers must explore other forms of adaptive emotion regulation [9].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study showed that the development of emotion regulation can explain the mechanism of daily influence that is stable throughout adulthood. The researchers must explore other forms of adaptive emotion regulation [9].…”
Section: Resultsmentioning
confidence: 99%
“…A tool used in this study to measure emotion regulation was the Emotion Regulation Questionnaire (ERQ) adapted from an instrument developed [5] According to [9] the results of the validity test with Pearson Correlation showed that the value of the reliability coefficient 0.780 and 59 items of the statement was valid. The researcher assessed the anxiety level using the Hamilton Rating Scale for Anxiety (HRS-A), developed by the Jakarta Biology Psychiatry group (KPBJ) in the form of Anxiety Analog Scale (AAS).…”
Section: IImentioning
confidence: 99%
“…Penelitian serupa juga dilakukan oleh Jangkup, Elim, Kandou (2015) yang menunjukkan bahwa pasien penyakit GGK yang menjalani hemodialisa <6 bulan memiliki tingkat kecemasan yang signifikan berat dibandingkan dengan yang menjalani hemodialisis >6 bulan.…”
Section: Pendahuluanunclassified
“…Patients undergoing hemodialysis every week need 12-15 hours for dialysis, or at least 3-4 hours per therapy [5]. This activity will continue throughout his life.…”
Section: Introductionmentioning
confidence: 99%
“…This first experience is a very important and very decisive factor for mental conditionsin the future. If someone's experience is lacking about hemodialysis, it tends to affect the increase in anxiety when facing hemodialysis [5].The state of dependence on the dialysis machine throughout his life results in changes in the lives of people with CRF. Health status, economic conditions, and the hemodialysis process itself can affect changes in the patient's life, all of which are one of the triggers or causes of stress.…”
Section: Introductionmentioning
confidence: 99%